Genomic Characterization of Multidrug-Resistant Acinetobacter baumannii in Pneumonia Patients in Kazakhstan - Vitaliy Strochkov; Vyacheslav Beloussov; Shynggys Orkara; Alyona Lavrinenko; Maxim Solomadin; Sergey Yegorov; Nurlan Sandybayev (Diagnostics)
Background/Objectives: Acinetobacter baumannii is an increasingly significant nosocomial pathogen causing severe infections globally. The emergence of multidrug-resistant A. baumannii strains has raised concerns about the efficacy of current treatment options. This study aimed to investigate the molecular epidemiology and antimicrobial resistance patterns of A. baumannii isolates from Kazakhstan. Methods: We collected nine A. baumannii isolates in 2022–2023 in Karaganda, Kazakhstan, which were then subjected to whole-genome sequencing (WGS) using the IonTorrent platform for genome characterization. Multilocus sequence typing (MLST) was used to classify the isolates into distinct clonal complexes. In addition, antibiotic susceptibility testing was conducted using the standard methods for a range of antibiotics commonly used against A. baumannii. Results: Our results revealed a high degree of genomic diversity among isolates from Kazakhstan, with multiple distinct classes identified: ST78 (n = 4, 44.4%), ST15 (n = 2, 22.2%), ST2 (n = 2, 22.2%), and ST193 (n = 1, 11%). MLST analysis showed that ST78Pas/1104Oxf (harboring blaOXA-72 and blaOXA-90 genes) were prevalent among the multidrug-resistant isolates. Based on the results of MLST, KL, and OCL, the analyzed isolates were assigned to specific international clones: IC2—ST2(Pas)-KL2/168-OCL1, IC4—ST15(Pas)-KL9-OCL7, and IC6—ST78(Pas)-KL49-OCL1. Notably, these isolates exhibited resistance to multiple antibiotics including meropenem, imipenem, gentamicin, amikacin, and ciprofloxacin. Conclusions: This study highlighted the complex molecular epidemiology of A. baumannii in Kazakhstan over a two-year period, underscoring the need for targeted surveillance strategies to monitor antimicrobial resistance patterns. The emergence and dissemination of multidrug-resistant strains within this timeframe emphasizes the importance of whole-genome sequencing as a diagnostic tool and underscores the challenges posed by these infections.